Answer: [tex]x=\frac{3}{10}[/tex]
Step-by-step explanation:
The expression is not written clearly. However, let's assume it is:
x+4/2+(x-3)/3=x+2/4+x+3/5
or
[tex]x+\frac{4}{2}+\frac{x-3}{3}=x+\frac{2}{4}+x+\frac{3}{5}[/tex]
Grouping similar terms:
[tex]x+2+\frac{x-3}{3}=2x+\frac{1}{2}+x+\frac{3}{5}[/tex]
Calculating the least common multiple (l.c.m) in the denominators of both sides of the equation:
[tex]\frac{3x+6+x-3}{3}=\frac{10x+5+6}{10}[/tex]
Applying cross product:
[tex]10(4x+3)=3(10x+11)[/tex]
Applying distributive property:
[tex]40x+30=30x+33[/tex]
Isolating [tex]x[/tex]:
[tex]x=\frac{3}{10}[/tex]